2013
DOI: 10.1007/s00167-013-2766-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of MRI in the diagnosis of meniscal tears in patients with chronic ACL tears

Abstract: The sensitivity for diagnosing a meniscal tear was significantly higher when the tear involved more than one-third of the meniscus or the anterior horn. The sensitivity was significantly lower for tears located in the posterior horn and for vertically oriented tears. Therefore, special attention should be given to the peripheral posterior horns of the meniscus, which are common sites of injury that could be easily missed on MRI. The high NPVs obtained in this study suggest that MRI is a valuable tool prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…MRI is a reliable tool for assessing meniscal tears and cartilage defects preoperatively, but it was reportedly more accurate for evaluating MMT than LMT. 30,31 It has also been reported that the sensitivity and negative predictive value for meniscal tears decrease in the presence of ACL tears, especially for LMT. 32 Thus, compared with MMT, the incidence of LMT in MRI studies may be underestimated in our series.…”
Section: Discussionmentioning
confidence: 96%
“…MRI is a reliable tool for assessing meniscal tears and cartilage defects preoperatively, but it was reportedly more accurate for evaluating MMT than LMT. 30,31 It has also been reported that the sensitivity and negative predictive value for meniscal tears decrease in the presence of ACL tears, especially for LMT. 32 Thus, compared with MMT, the incidence of LMT in MRI studies may be underestimated in our series.…”
Section: Discussionmentioning
confidence: 96%
“…Sensitivities and specificities of over 80% have been described for detection of meniscal tears when compared with arthroscopy as a gold standard [22–24]. …”
Section: Discussionmentioning
confidence: 99%
“…Imaging at or around the posterior meniscal horn can be challenging. Sharifah et al described significantly lower sensitivities when the meniscal tears were located in the posterior horn [22]. In the same vein, Naranje et al reviewed the accuracy of MRI for diagnosis of meniscal lesions [23].…”
Section: Discussionmentioning
confidence: 99%
“…Though the ACL serves as the primary restraint to both anteroposterior and rotational stability, especially at low flexion angles, other surrounding knee structures contribute to joint stability [48]. Concomitant injury to medial or lateral meniscus is reported to be present in 16 to 82 % in acute ACL injuries and up to 96 % in chronic ACL injuries [49][50][51]. In addition to load distribution function, menisci also play a role in joint stability.…”
Section: Treatment Of Associated Injuriesmentioning
confidence: 99%